Quality of water discharge from shrimp hatcheries and its impact on the surrounding coastal environment - Muralidhar, M; Gupta, B P (Indian Journal of Fisheries, 2011)
Availability of quality shrimp seed is a prerequisite for successful shrimp culture. Mass production of post larvae in the hatcheries need large quantities of seawater, which again goes back to the sea/backwaters as wastewater. In order to assess the quality of discharge water from the hatchery and its impact on the surrounding environment, water samples from two commercial shrimp hatcheries located along the coast of Tamil Nadu and Andhra Pradesh were analysed for various physico-chemical parameters, pesticides and heavy metals. Though there was some increase in values of some of the parameters in discharge water as compared to filtered seawater, levels of all parameters were well within the permissible limits as prescribed by the Ministry of Environment and Forests. Practically, there was no significant increase in the levels of pesticides and heavy metals in the outfall regions compared to intake water.